The fall in oil prices and its impact on the Colombian economy (2015)
The price of oil has dropped considerably over the past nine months. The Brend variety, the benchmark for Colombia, dropped from US$ 115 to US$ 55 a barrel, between June 2014 and March 2015. The lowest price was recorded on January 28 of this year, when it traded at US$44.45 a barrel. Such a rapid and pronounced fall had not happened before. The price variation and the way in which it took place were due as much to factors of demand as of supply.